1993
DOI: 10.1126/science.8424175
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Sphingomyelin Signaling Pathway in Intact EL4 Cells and in a Cell-Free System By IL-1β

Abstract: The mechanism of interleukin-1 (IL-1) signaling is unknown. Tumor necrosis factor-alpha uses a signal transduction pathway that involves sphingomyelin hydrolysis to ceramide and stimulation of a ceramide-activated protein kinase. In intact EL4 thymoma cells, IL-1 beta similarly stimulated a rapid decrease of sphingomyelin and an elevation of ceramide, and enhanced ceramide-activated protein kinase activity. This cascade was also activated by IL-1 beta in a cell-free system, demonstrating tight coupling to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
222
0

Year Published

1996
1996
2002
2002

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 422 publications
(232 citation statements)
references
References 50 publications
10
222
0
Order By: Relevance
“…To determine exogenous stimulation of sphingomyelin hydrolysis by ligand-induced receptor activation, LNCaP cells were exposed to IL-1b, a well known activator of the sphingomyelin pathway in other cellular systems (Kolesnick & Golde, 1994;Mathias et al, 1993;Santana et al, 1996). A 30 min treatment with 1 ng ml 71 IL1-b produced a marked reduction of sphingomyelin levels paralleled by enhanced formation of ceramide (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…To determine exogenous stimulation of sphingomyelin hydrolysis by ligand-induced receptor activation, LNCaP cells were exposed to IL-1b, a well known activator of the sphingomyelin pathway in other cellular systems (Kolesnick & Golde, 1994;Mathias et al, 1993;Santana et al, 1996). A 30 min treatment with 1 ng ml 71 IL1-b produced a marked reduction of sphingomyelin levels paralleled by enhanced formation of ceramide (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…Three forms of SMases are candidates for SM hydrolysis. Acid SMase (pH optimum 4.5 ± 5.0) has been associated in apoptosis signaling triggered by TNFa (Wiegmann et al, 1994), antiFas (Cifone et al, 1994), and anti-CD28 (Boucher et al, 1995); activation of a membrane bound neutral SMase (pH optimum 7.4) has also been described with TNFa (Wiegmann et al, 1994), anti-Fas antibody (Tepper et al, 1995), IL-1b (Mathias et al, 1993) and daunorubicin ; finally, a cytosolic neutral SMase has been implicated in vitamin D3 induced differentiation (Okazaki et al, 1994). A recent study by Kolesnick's group clearly demonstrated that acid SMase-deficient human lymphoblasts as well as lung endothelium, thymus and spleen of acid SMase knockout mice are defective in IRinduced apoptosis (Santana et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…indeed several mediators known to increase the intracellular levels of ceramide are involved in the early immune response, i.e., TCR triggering, IL-1␤, TNF-␣, IFN-␥, and CD28 ligation (10,(12)(13)(14)(15)(32)(33)(34). When the T cell forms Ag-specific conjugates with APC, a supramolecular activation cluster is observed at the T-APC contact zone.…”
Section: Discussionmentioning
confidence: 99%